Partial Clinical Remission in Type 1 Diabetes Mellitus: Frequency and Influencing Factors of its Occurrence - Dr. Salah Mahdi Ali; Dr. Ahmed Mohemed Aulawy; Dr. Muayad Salih Hammza (Open Journal of Physicians and Surgeons, 2024)
Background: The clinical remission or what is called honeymoon period is a phase in type 1 diabetes mellitus in which the patient show good metabolic control of his disease on a minimum doses of insulin and decrease of his HbA1C value to near normal levels. Objectives: To estimate the frequency of partial clinical remission and the factors which may affect its occurrence. Methods: A non- randomized prospective longitudinal study done in Central Child’s Teaching Hospital ,we enrolled 75 newly diagnosed patients and followed them for about 10 months we record the anthropometric data and clinical characteristics for each patient and thereafter at timely intervals which included HbA1c, insulin dose, body mass index ,C-peptide level and pubertal stage. Results: Out of the 75 patients 45(60%) males and 30 (40%) females , 38 (50.6%) of them show remission and 37(49.4%) did not show remission, the occurrence of partial clinical remission (PCR) found to be positively affected by initial insulin dose and the basal C-peptide level(p. value <0.05) and its duration found to be the longer and earlier in the age group of 5-10y and shorter in those younger than 5y. Conclusions: Almost half of newly diagnosed patient develop partial clinical remission, factors may affect its occurrence include initial insulin dose and basal C- peptide level and the range of duration of remission (42-150) days.